Penguatan Peran Posyandu dalam Pencegahan Stunting di Desa Tegalrejo Pulung Ponorogo dengan Mengguakan Metode CBD (Ceramah, Brainstroming dan Demontrasi) - Sekar Wulandari; Mariana Mariana (Social Science Academic, 2025)
Stunting is a nutritional problem caused by a lack of balanced nutritional intake experienced in the early period of toddler development and growth. Efforts to prevent stunting in toddlers are a serious problem in a country, one of the many efforts implemented is through the posyandu program guided by posyandu cadres. The purpose of this study was to improve posyandu in providing information about stunting using the CBD method. The population in this study is the community, especially parents of toddlers or pregnant women in Tegalrejo Village, Pulung District, Ponorogo Regency. This activity includes surveys and carrying out socialization on efforts to reduce the number of stunting in toddlers. The research results obtained are that the CBD method can increase knowledge, attitudes and alternative actions chosen by posyandu cadres in providing information about stunting.